Health Belief Regarding Leisure Time Physical Activity and Nutritional Attitude: Are They Related in Athletic and Sedentary University Students - Aktaş Üstün, Neslişah; Üstün, Ümit Doğan; Işık, Utku; Yapıcı, Adem (Progress in Nutrition, 2020)
Study Objectives: The present study aimed to investigate the differences in the perception of health belief regarding leisure-time physical activity and nutritional attitudes of athletic and sedentary university students. Besides, analyzing the correlations between the phenomena was another aim. Materials and Method: The study was designed as a cross-sectional quantitative study, and 286 university students from Hatay Mustafa Kemal University participated in the study. In analyzes of the data independent samples t-test and Partial Correlation analyzes were used. Results: As a result, this study showed that only self-efficacy makes a difference in the health belief regarding leisure-time physical activity for the athletes. Besides, the health belief regarding leisure-time physical activity and nutritional attitude correlates in both athletic and sedentary samples. Conclusion: To achieve substantive health benefits, efforts to increase leisure time physical activity and healthy nutritional attitudes should be encouraged.